The Spirituality at the Heart of the Catholic Charismatic Renewal Movement - Moran, Michelle (Transformation, 2013)
This article focuses on the spirituality at the heart of the Catholic Charismatic Renewal. The emergence of this ‘renewal movement’ is set within the wider historical context of the Roman Catholic Church in the 20th century. This is also linking in with the current of grace which birthed the worldwide Pentecostal movement. The nature of the Charismatic Renewal is unique as it is not a single unified worldwide movement. It is rather a stream of grace destined to rejuvenate every part of the Church’s life.